Dynamics of sting-jet storm "Egon" over continental Europe using convection-permitting simulations - Eisenstein, Lea; Pantillon, Florian; Knippertz, Peter; Pinto, Joaquim G. (2023)
Cyclonic windstorms belong to the most destructive natural hazards in Europe. The associated strong surface wind gusts are often connected with the cold and warm conveyor belts, as well as with frontal convection. Moreover, intense Shapiro-Keyser cyclones can be accompanied by the occurrence of a so-called sting jet, which is a distinct air stream that descends from the cloud head in the mid-troposphere into the frontal-fracture region and can cause very intense near-surface gusts. There is still some debate in the community regarding what mechanisms cause or contribute to the occurrence of a sting jet. Furthermore, the existing literature is almost entirely dedicated to sting jet case studies over the North Atlantic, the British Isles, and the North Sea. This work focuses on windstorm Egon (12-13 January 2017), which is the first documented sting jet case over continental Europe. To analyse the storm, ICON (ICOsahedral Nonhydrostatic model) in limited area mode is used for simulations with horizontal grid spacings down to 1.6 km. With such a high resolution, convective and mesoscale instabilities are explicitly resolved and the orography is well represented. Lagrangian trajectories calculated with the LAGRANTO software confirm the presence of a sting jet. They further show consistency with most of the widely accepted characteristics of sting jets, namely descent on constant wet-bulb potential temperature surfaces and acceleration during the descent. Moreover, a possible contribution of conditional symmetric instability (CSI) and evaporative cooling is detected, two processes suggested by previous studies. However, no agreement is found regarding the expected changes in relative humidity values, which do not show the typical drying Additionally, the sensitivity of sting jet trajectories is analysed with respect to the calculation and selection of trajectories. While all combinations show a sting jet with consistent characteristics, its strength and the representation of CSI deviate significantly in some cases. ...